QUALITY OF LIFE IN FEMALE PATIENTS WITH TUBERCULOSIS DURING HORMONE MODULATION THERAPY - A. E. Grabarnik; O. G. Zhuchenko; Z. A. Zangieva; V. M. Esikova (Туберкулез и болезни лёгких)
The normal function of reproductive organs should be regarded as one of the most important indicators of women’s health. During combination therapy, female patients with tuberculosis, regardless of the location of the process, have significant ovarian functional impairments contributing to different menstrual dysfunctions, as well as anatomic and functional changes in the reproductive organs. This all is certain to negatively impact the quality of life in women suffering from tuberculosis.In assessing the quality of life, it has become obvious that its low indicators are noted in virtually every three patients with tuberculosis.Hormone modulation therapy with due regard for hormonal changes, the presence of hormone-dependent diseases, the pattern and location of tuberculous lesion, and the specific features of performed specific therapy results in reproductive system rehabilitation and improves the responsiveness of the body as a whole, which is accompanied by a clear increase in the quality of life in this contingent of patients.